Use of an Algorithm for Assessment and Treatment of The Upper Extremity Post Stroke: A Case Study. Issue 1 (2nd January 2015) - Ouellette, Debra S.; Okamoto, Susie Wong; Rosario, Emily R.
ABSTRACT The objective of this study was to identify movement impairments and plan effective treatments using an evidence-based algorithm. A single subject case study was completed to demonstrate the application of the Neurologic Upper Extremity Recovery Algorithm (NUERA), which integrates the analysis of patient alignment, along with movement of the trunk, ribcage and scapula. The Action Research Arm Test (ARAT) was used for standardized assessment and to assist in analyzing the patient's movement along with the nonstandardized clinicians assessment of movement. Using the NUERA, the patient's upper extremity control improved as demonstrated by a 78% improvement in the ARAT score from a 27 at initial assessment to 48 (57 possible) following 2 months of treatment, along with the achievement of the patient's goals. Use of the NUERA for the assessment and treatment of the upper extremity poststroke has promising utility.